Lysosomes’ fallback strategies: more than just survival or death - Wang, Quan; Wang, Ruolin; Hu, Haihui; Huo, Xiaoqing; Wang, Fulong (Frontiers in Cell and Developmental Biology, 2025)
Lysosomes are heterogeneous, acidic organelles whose proper functionality is critically dependent on maintaining the integrity of their membranes and the acidity within their lumen. When subjected to stress, the lysosomal membrane can become permeabilized, posing a significant risk to the organelle’s survival and necessitating prompt repair. Although numerous mechanisms for lysosomal repair have been identified in recent years, the progression of lysosome-related diseases is more closely linked to the organelle’s alternative strategies when repair mechanisms fail, particularly in the contexts of aging and pathogen infection. This review explores lysosomal responses to damage, including the secretion of lysosomal contents and the interactions with lysosome-associated organelles in the endolysosomal system. Furthermore, it examines the role of organelles outside this system, such as the endoplasmic reticulum (ER) and Golgi apparatus, as auxiliary organelles of the endolysosomal system. These alternative strategies are crucial to understanding disease progression. For instance, the secretion and spread of misfolded proteins play key roles in neurodegenerative disease advancement, while pathogen escape via lysosomal secretion and lysosomotropic drug expulsion underlie cancer treatment resistance. Reexamining these lysosomal fallback strategies could provide new perspectives on lysosomal biology and their contribution to disease progression.